Lifetime measurements of the low-lying excited states of 208Po. (May 2020) - Kocheva, D.; Yaneva, A.; Kalaydjieva, D.; Rainovski, G.; Jolie, J.; Pietralla, N.; Beckers, M.; Blazhev, A.; Bussmann, L.; Cappellazzo, M.; Dewald, A.; Diel, F.; et al.
Abstract: In this study we present the preliminary results about the lifetimes of the 2 2 +, 4 1 + states of 208 Po and the upper limit of the lifetime of the 2 1 + state. For measuring the lifetimes of the 2 1 + and 4 1 + states the Recoil Distance Doppler Shift (RDDS) method and for the lifetime of the 2 2 + state the Doppler Shift Attenuation method (DSAM) were used. The resulting absolute transition strength B ( M 1 ; 2 2 + → 2 1 + ) ≥ 0.122 ( 20 ) μ N 2 reveals the predominant isovector nature of the 2 2 + state of 208 Po.